The Role of School Committees in Optimizing Administration in Elementary Schools - Dinda Oktaviana; Shalwa Rizkya Shalsabila; Tin Rustini (CV. Rayyan Dwi Bharata, 2023)
The school committee plays an important role in optimizing administration in elementary schools. The purpose of this study is to examine the role of school committees in improving school governance and creating an optimal learning environment. The research method used is qualitative research with literature study methods by collecting data from various sources. The results showed that the role of the school committee in improving administration includes financial supervision and management, work plans and programs, performance evaluation, education quality coaching, and cooperation with parents and other stakeholders. The school committee actively carries out its roles and duties can create a better learning environment and ensure the success of the educational process in primary school.